The Example Non Example Learning Model and Its Influence on The Ability to Understand Two-Dementional Figure in Mathematical Concepts of Elementary School Students - Adinda Khairunisa; Ima Mulyawati (Universitas Pendidikan Mandalika, 2023)
This study aims to analyze the effect of the Example Non-Example learning model on the ability to understand mathematical concepts in third-grade elementary school students. This research method used True Experiments with a quantitative approach. The sample used was Simple Random Sampling. The validity test employed Point Biserial Correlation, which had 30 multiple-choice questions with 20 valid and ten invalid ones. At the same time, the reliability test used the KR-20 formula. For the data analysis of the requirements test, the normality test employed the Chi-Square test; the results obtained from the control class were at the pre-test 6.63 < 11.1 and at the post-test 12.55 < 12.6. In the experimental class, the results were obtained at the pre-test 9.99 < 12.6 and the post-test 25.26 > 12.6. In conclusion, all data is typically distributed. At the same time, the homogeneity test used the Fisher test to test the hypothesis using the T-Test and Effect Size test. Based on the results of the study, there was an influence of the Example Non-Example learning model on the ability to understand mathematical concepts in the two-dimensional figure material for third-grade students at SDN 07 Bojong Gede.